COVID-19 & Mental Wellbeing of School Enrolled Teens in Foothills of Himalaya - Chaudhary, Deepshikha; Semwal, Jayanti; Sharma, Neha; Srivastava, Malini; Avinash, Priya Ranjan; Bahuguna, Abhinav (Indian Journal of Community Health, 2024)
Introduction: COVID-19 pandemic resulted in a national lockdown and physical contact was avoided that substantially changed people’s lives. The overall impact of lockdown during COVID-19 was negative on the general & mental health of adolescents. During the COVID-19 pandemic, there is a 25% massive increase in the global prevalence of anxiety and depression. Aims & Objectives: To assess anxiety & depression and their association with socio-demographic factors during the COVID-19 pandemic among school-going adolescents. Methodology: Using two simple random sampling, a cross-sectional study was conducted among 690 school-age adolescents (14 to 19 years) in four Nagar Palikas of the district of Dehradun. The questionnaire includes sociodemographic section, GAD-7, PHQ-2, Modified version of CoPaQ and coping strategies. Result: In study it’s been found that more than half of the participants were facing symptoms of anxiety and 58.7% of participants had a major depressive disorder likely. 78% participants used phone and internet f/b watching TV (73.8%) and sleeping (68.1%). Conclusion: In order to combat adolescents’ mental illness, we advise the creation of support groups at the family and school levels as well as prompt intervention through the revision of current strategies or formulation of new legislation